Dynamics of work disability and pain - Arie Kapteyn; James P. Smith (Institute for the Study of Labor (IZA), 2006)
This paper investigates the role of pain in affecting self-reported work disability and employment of elderly workers in the US. We investigate pain and its relationship to work disability and work in a dynamic panel data model, using six biennial waves from the Health and Retirement Study. We find the dynamics of the presence of pain is central to understanding the dynamics of self-reported work disability. By affecting work disability pain also has important implications for the dynamic patterns of employment.
Keywords: J28; I12; C81; 330; work limiting disability; health; Erwerbsunfähigkeit; Ältere Arbeitskräfte; USA